2019
DOI: 10.7554/elife.41728
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal morphologies built for reliable physiology in a rhythmic motor circuit

Abstract: It is often assumed that highly-branched neuronal structures perform compartmentalized computations. However, previously we showed that the Gastric Mill (GM) neuron in the crustacean stomatogastric ganglion (STG) operates like a single electrotonic compartment, despite having thousands of branch points and total cable length >10 mm (Otopalik et al., 2017a; 2017b). Here we show that compact electrotonic architecture is generalizable to other STG neuron types, and that these neurons present direction-insensitive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 77 publications
(123 reference statements)
6
19
0
Order By: Relevance
“…However, studies employing multicompartmental neuronal models have also demonstrated a remarkable degree of flexibility in a neuron's ion channel distributions that can combine to elicit similar physiological outcomes Basak and Narayanan 2018b;Otopalik et al 2017b;Otopalik et al 2017a;Otopalik et al 2019;Migliore et al 2018;Beining et al 2017;Taylor et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies employing multicompartmental neuronal models have also demonstrated a remarkable degree of flexibility in a neuron's ion channel distributions that can combine to elicit similar physiological outcomes Basak and Narayanan 2018b;Otopalik et al 2017b;Otopalik et al 2017a;Otopalik et al 2019;Migliore et al 2018;Beining et al 2017;Taylor et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A second class of studies have assessed pathology-induced or behaviorally relevant dendritic remodeling (atrophy or hypertrophy) in neuronal structures (van Elburg and van Ooyen 2010; van Ooyen et al 2002; Narayanan and Chattarji 2010; Narayanan et al 2005; Dhupia et al 2014). A third class of studies explored the implications for intrinsic morphological heterogeneities within a neuronal subtype(Krichmar et al 2002;Ferrante et al 2013;Beining et al 2017;Weaver and Wearne 2008;Otopalik et al 2017b;Otopalik et al 2019;Otopalik et al 2017a;Schaefer et al 2003).…”
mentioning
confidence: 99%
“…Thus dendritic shape and synapse placement can have a strong influence on neuronal computational performance (reviewed in 62, 63 ). However, recent studies in the stomatogastric ganglion of crabs showed that the specific tapering of dendritic branches can effectively compact elaborate dendritic structures to a uniform electrotonic compartment, thus strongly reducing the impact of synapse positioning along a dendritic arbor on signal integration and ultimately spike output 6466 . Conversely, experimentally reduced dendritic arbor complexity of Drosophila flight motorneurons still supports astonishingly normal neuronal performance, and only behaviors requiring fine precision appear to be negatively affected 67 .…”
Section: Discussionmentioning
confidence: 99%
“…Active conductance in dendrites can normalize the efficacy of distal synapses and democratize dendrites by making distal and proximal synapses equally efficient in influencing somatic firing. Strong dendritic tapering attenuates electrotonic attenuation to such an extent that the dendritic tree becomes approximately isopotential (Otopalik et al, 2019 ). Therefore, dendritic structures may avoid attenuation.…”
Section: Biologically Motivated Backgroundmentioning
confidence: 99%